The challenges of an impact-oriented fintech entrepreneur: what are they and how to overcome them? - Freischlag, Bruno Luis Avila (Universidade do Vale do Rio dos Sinos, 2022)
Social entrepreneurship it is considered a trendy twenty-first century phenomenon, endorsed by worldwide know personalities such as the Muhammad Yunus, one that forever changed the concepts of social entrepreneurship and financial inclusion. Yet, despite his unquestionable achievements, there is still about 1.7 billion adults considered unbanked worldwide. Financial exclusion deprives individuals of access to useful and affordable financial products and ser-vices that meet their needs, leading to high levels of poverty and undeveloped. Digital Finan-cial Inclusion, defined as digital access to and use of formal financial services by excluded and underserved populations, it is now considered as a modern solution and a powerful allied to the financial inclusão agenda. Fintechs is characterized by the use of technologies to finan-cial services, hence, its potential to deal with problems related to financial exclusion is increas-ingly highlighted by researchers and practitioners alike. Nonetheless, the topic of financial inclusion and fintechs is yet in its infancy, leading to the existence of several theoretical and practical gaps. The importance of financial inclusion for society, and the potential of fintechs as promoters of this inclusion makes very clear the need for instruments that help in the devel-opment of businesses that especially solve the problem of financial inclusion. This research aims to address this gap by asking: what the challenges of an inclusion-oriented entrepreneur? Therefore, this research main objective is to propose an artifact that compiles the challenges and the possible course of action to the main challenges perceived by these entrepreneurs. To achieve the objective, this research makes use of the Design Science Research methodology, by proposing an artefact. It is believed that the choice of method is appropriate for its power to solve real problems in a collaborative way between the researcher and entrepreneurs, and for the high practical applicability, also allowing continuous improvements of the proposed model in future research. This research raises awareness to a yet very unexplored topic by the literature, having a theoretical contribution validating some of the challenges already encoun-tered in the literature, but also discussing several others that have not yet been explored. Not only that, but the theoretical contribution is also evidenced by the advance in the factors that form the entrepreneurial intention, since the challenges are linked to the perceived viability of the business by the entrepreneur. Going even beyond, this is one of the first research that also has a concern to bring a practical solution to the most recurrent challenges faced by the entre-preneurs. As for a practical contribution, it is expected that the proposed artifact can have a meaningful impact on the emergence of new inclusion-oriented fintech by allowing the entre-preneurs to understand what the potential challenges are ahead of him and what are course of actions that he can to overcome them more easily.
Keywords: Inovação social; Empreendedorismo social; Inclusão financeira; Fintech; Design Science Research; Social innovation; Social entrepreneurship; Financial inclusion; ACCNPQ::Ciências Sociais Aplicadas::Administração